Challenges of Merchandising Strategies in Fashion Retailing - A Study on Private Labels Vs Manufactured Brands - Krishnan, N. V. H.; Prasanna Venkatesh, S. (Indian Journal of Marketing, 2008)
With the constant Rising income, Changing demographics and Consumer taste are driving the growth of more than 30 per cent of the modern retail formats, and it is expected to grow another 9 percent in the year of 2010. India is more attractive than ever to global retailers. India's economic growth, forecasted at 9-10 percent of GDP 2007-08, continues to support the retail industry. The estimated $350 billion retail market is expected to grow at 13 per cent and the top five retailers account for less than 2 per cent of the modern retail market. And with one billion people, it is second largest population in the world. Clothing, Textile and Fashion accessories segment constitute significant portion (35%) contributing to the growth of Indian retail industry. Competitions in this segment are intensified as many as players were entered into this segment constitute both unorganized as well as organized players. All these players are using a different kind of strategies like Store ambience, Store Atmospherics, Aesthetics of the store, Visual Merchandising, Discounted pricing, value added services etc., to attract more footfalls to patronage their customers. All these strategies will become meaningless unless the store has right mix of merchandise in terms of varieties, assortment, colour, and support levels to satisfy the target customers. Therefore this research is an attempt to find out the challenges of merchandising strategy followed by fashion retailing. Because the fashion retailing is now harder than ever to predict the next season's breakthrough fashion trend. Retailers of clothing, shoes, and accessories operate in a fast-moving market where many different styles and trends simultaneously influence tastes. Both basic wardrobe staples and high-fashion apparel are affected by regional differences in sizes and preferences. A retailer's ability to respond quickly to shifting patterns of demand depends heavily upon how well it controls its supply chain, collaborates with suppliers, and manages its merchandise. Retailers have to quickly introduce new lines to maintain high sales and out-pace the competition.